(untitled) (Ágora Journal, 2022)
The analysis of the days following the incorporation of the provinces into the Empire of Brazil can point the ways to understand the conditions that established the new political pact. With this intention, the article recovers elements of the political dynamics of the province of Maranhão between July and September of 1823, time of the “adherence”, of the the first Junta of Government formation, and of important purges, components of a first arrangement under which it based the disputes that would move the province in the following years until, at least, 1831. To this end, it initially resorts to the dialogue maintained by Admiral Cochrane – official responsible for the capitulation – with some Portuguese authorities; then, the focus falls on the question of the “Portuguese”, taken in a retrospective sense, since the first news about Independence in Rio de Janeiro, and also as a guideline for the analysis of a set of arrests, dismissals and expulsions, concentrated in September 1823.